High risk factors for craniosynostosis during pregnancy: A case-control study - Sotirios Plakas; Evangelos Anagnostou; Angelos Christos Plakas; Maria Piagkou (Elsevier, 2022)
Background: Craniosynostosis is a birth defect involving premature cranial sutures' fusion with an increasing prevalence and unknown underlying causes in nearly 80% of cases. The current study investigates a series of high-risk factors associated with a non-syndromic craniosynostosis. Methods: Ninety-seven (97) children were included in the retrospective case-control study, 62 controls and 35 with craniosynostosis. A questionnaire with 143 questions was used in face-to-face interviews. After univariate analyses, stepwise multivariate logistic regression analysis was implemented. Results: In craniosynostosis group, 3 out of 4 were male subjects and 2 out of 3 born with caesarian section. History for central nervous system abnormalities in their younger siblings, low birth weight, extended use of mobile phone from the parents and medications' use differed significantly between craniosynostosis and control group. After adjustment for all factors, only maternal medication use (aOR 6,1 [2.1 - 19], CI 95%) and oral progesterone intake (aOR 4 [1.2 - 14], CI 95%) were significantly associated with an increased risk in craniosynostosis group. Conclusion: The maternal medications' use and particular oral progesterone intake is associated with an increased risk for non-syndromic craniosynostosis. However, due to the study's limitations, further research is warranted.